Digital Transformation Acceleration and Character-Based Excellent Human Resources Capacity in Fostering Sustainable Rural Economy Based on Tourism and Islamic Economics: A SLR - Mufti Agung Wibowo; Setya Indah; Abdul Aziz; Ari Siswati; Agung Wibowo (Journal of Social Research, 2026)
This study examined the acceleration of rural economic transformation through the integration of digital technology, human resource capacity, sustainable tourism, and Islamic economic principles. The background of this research was rooted in the persistent development gap between urban and rural areas, particularly in digital access, managerial capacity, and sustainable economic structures within village-based enterprises. The objective of this study was to synthesize existing literature to develop a comprehensive understanding of how digital transformation and character-based human resource capacity contribute to sustainable rural economic development within tourism and sharia-based frameworks. The method used was a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. Data were collected from reputable databases such as Scopus, Web of Science, and Google Scholar, covering studies published between 2010 and 2025. A total of 100 selected articles were analyzed using thematic synthesis to identify patterns, relationships, and conceptual developments. The results showed that digital transformation significantly improved rural economic efficiency, particularly through the digitalization of village-owned enterprises (BUMDes) and marketing innovation. However, its effectiveness strongly depended on human resource readiness, governance quality, and digital literacy. Furthermore, sustainable tourism and Islamic economic principles were found to enhance environmental protection, ethical governance, and inclusive economic distribution. In conclusion, rural development is most effective when digitalization, human capital development, and value-based economic systems are integrated holistically. This study contributes a synthesized conceptual framework for sustainable rural transformation and provides policy implications for strengthening digital ecosystems, human capacity, and sharia-compliant rural economic models.